2002
DOI: 10.1159/000063606
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Amyloid Angiopathy, White Matter Lesions and Alzheimer Encephalopathy – A Histopathological Assessment

Abstract: To test the hypothesis that the cerebral amyloid angiopathy (CAA) of Alzheimer’s disease (AD) is quantitatively associated with white matter lesions (WML), the brains of 63 demented patients exhibiting varying degrees of Alzheimer encephalopathy (AE) were examined, along with those of 10 nondemented control cases. The ratio of amyloid-positive to amyloid-negative vessels in the leptomeninges of the frontal pole from each patient was calculated subsequent to microscopical examination, and the severity of WML wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
61
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 24 publications
6
61
3
Order By: Relevance
“…No significant correlations were seen between severity of overall cortical AD pathology and OD ratios, in line with previously observed lack of correlation between the grey-and white matter pathology (Brun and Englund, 1986;Sjobeck and Englund, 2003). The association between WMD, central white matter arteriolosclerosis and CAA in the meninges and outer cortex is notable (Haglund and Englund, 2002;Tian et al, 2004). The number of small vessels correlates inversely with severity of WMD, further indicating the association with vascular manifestations .…”
Section: Different White Matter Pathologies In Adsupporting
confidence: 83%
See 1 more Smart Citation
“…No significant correlations were seen between severity of overall cortical AD pathology and OD ratios, in line with previously observed lack of correlation between the grey-and white matter pathology (Brun and Englund, 1986;Sjobeck and Englund, 2003). The association between WMD, central white matter arteriolosclerosis and CAA in the meninges and outer cortex is notable (Haglund and Englund, 2002;Tian et al, 2004). The number of small vessels correlates inversely with severity of WMD, further indicating the association with vascular manifestations .…”
Section: Different White Matter Pathologies In Adsupporting
confidence: 83%
“…Severity of WMD has been shown to correlate with number of microvessels in the white matter, i.e., more pronounced changes are associated with fewer vessels , but no association has been shown between overall severity of cortical AD pathology and severity of WMD (Brun and Englund, 1986;Haglund and Englund, 2002). The congophilic amyloid angiopathy (CAA) of AD, however, has been shown to correlate with severity of WMD in AD (Haglund and Englund, 2002), suggesting a vascular link in the pathogenesis of the white matter pathology.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44] Pathologic examination of WMH in the brains of cases with CAA suggests an ischemic origin. 9,45,46 One serial imaging study in patients with SVD showed that small silent acute infarcts approach the signal characteristics of WMH within a period of 16 weeks, indicating that WMH may partly be formed by tiny infarcts. 47 Increased WMH volume in patients with CAA has been related to lower cerebral perfusion.…”
Section: White-matter Hyperintensitiesmentioning
confidence: 99%
“…WML may be prominent in Alzheimer disease attributed to a combination of local WM ischemia, sometimes mediated by congophilic amyloid angiopathy, and axonal loss secondary to cortical neurodegeneration. 11,13,14 Extravasation of serum proteins has also been demonstrated in the WML of Alzheimer disease, 15 Binswanger disease, 16 and in "incidental" lesions suggesting abnormal blood-brain barrier function. In DSCL we have previously shown evidence of tissue hypoxia.…”
mentioning
confidence: 99%